Therapeutic Role of Clinical Inertia among Patients with Degenerative Arthritis - Noor Ullah Khan, Mazhar Arshad, Anam Zafar, Afifa Ehsan, Muhammad Haris Idrees, Syed Zahra Gillani (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: In underdeveloped countries, clinicians face obstacles in achieving goals of management in conditions such as diabetes, hypertension, stroke, arthritis, sciatica, and lower back pain. In practice, clinical inertia plays a notable role as a factor that leads to inadequate management of chronic diseases. Clinical inertia has on no occasion been elaborated in musculoskeletal disorders in Pakistan. Consequently, the purpose of this study was to check the occurrence of clinical inertia among patients with degenerative arthritis and to know the medical errors associated with it. Methods: This cross-sectional study was conducted from April 2022 to December 2022 and included 150 study participants suffering from degenerative osteoarthritis by non-probability convenient sampling. Data were collected by retrospective chart reviews from private physical therapy clinics in Lahore. Friedman ANOVA was used for comparison between NPRS at the time of the first visit; at week 1 and week 2. Results: The findings of this study suggest that there is a significant difference (P ≤ 0.000) between the pain of study participants at the time of the first visit, after one week, and after the second week. The study also showed that the charts of the research participants receiving treatment did not mention the range of motion associated with degenerative osteoarthritis which is considered one of the crucial goals in patients suffering from degenerative osteoarthritis. Practical Implication: There is a dire need to have an in-depth knowledge of clinical inertia and its factors which will ultimately help to develop specific strategies to minimize reflexive errors that play a causative role in clinical idleness. Conclusions: There is a difference in pain intensity of patients in the first week and during the second week but there is a high risk of clinical inertia in physical therapy practice related to lack of knowledge. Keywords: Degenerative Arthritis, Inertia, Joint Diseases, Musculoskeletal Diseases, Osteoarthritis, Physiotherapy, and Physical Therapy.